Evaluasi Pendidikan: Analisis Kualitas Tes Sumatif di SMP Modern Al Rifa Ie Malang - Hidayah, Susilo; Dyah Capriatin, Chalishah; Aminatuz Zuhriyah, Indah (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
This article aims to analyze the quality of even semester final summative questions of PAI subjects in class VIII of Modern Al Rifa Ie Junior High School in Malang in the 2023/2024 academic year. This research is a quantitative descriptive research. The results showed that the quality of question items based on validity, on short description questions there are 13 valid items, true-false questions there are 6 questions, the type of long description questions there are 5 items. The quality of question items based on reliability, on the short description questions the questions used have a high reliability coefficient of 0.798, true-false questions have a high reliability coefficient of 0.609, while the type of long description questions have a low reliability coefficient of 0.560. The quality of questions based on the level of difficulty, in the short description question there is 1 difficult item, 2 medium items, and 17 easy items. In true-false questions and long descriptions, all questions are categorized as easy items. The quality of questions based on differentiating power, in the short description question there are 12 items that have poor differentiating power, 2 items have sufficient differentiating power, 3 items have good differentiating power, and 3 items have excellent differentiating power. For the results of the analysis on true-false questions, there are 6 items that have poor differentiating power, 1 item has sufficient differentiating power, and 3 items have good differentiating power. As for the long description items, there are 2 items that have poor differentiating power, 2 items have sufficient differentiating power, and 1 item has excellent differentiating power.